Analisis Efisiensi dan Efektifitas Keuangan Desa/Nagari Kabupaten Tanah Datar Sumatera Barat - Afridian wirahadi ahmad; Gustia Eka Putri (Universitas Andalas, 2019)
This study aims to evaluate the level of efficiency and effectiveness of the use of village funds in villages / nagari located in Tanah Datar District, West Sumatra. Sources of village development funding come from village funds, village fund allocation and local revenue. The object of the study was 75 villages in Tanah Datar District using purposive sampling. The data analysis technique is used by Kepmendagri Number 690.900-327 concerning the criteria for evaluating the performance of financial statements. The results showed that the level of Nagari financial efficiency of 92.90% was included in the inefficient category. While the effectiveness level of 83.41% which is included in the category is quite effective.